Trichlorfon for Treatment of Cutaneous Habronemosis - Evaluation of Intravenous Regional Perfusion in the Distal Equine Limbs - Lino, Daniel Carneiro; de Morais, Divino Fábio; de Souza, Pedro Figueiredo Bastos; Moreira, Igor Louzada; Reis, Luiza de Siqueira Almeida; Teixeira Neto, Antônio Raphael; Dallago, Bruno Stéfano Lima; Gallo, Marco Aurélio; Campebell, Rita de Cassia (Acta Scientiae Veterinariae, 2022)
Background: Equine cutaneous habronemiasis is common in the distal regions of the limbs. Organophosphates, applied systemically, one previously used treatment, which is highly effective, but currently in disuse, due to the risks of intoxica- tion. Regional perfusion is a potential technique for distal limb wounds, since, in addition to being used in low doses, it prevents systemic circulation of the drug and possible intoxication, and has a lower treatment cost. The current work aimed to perform clinical, laboratory, and venography evaluations of the use of trichlorfon in regional intravenous perfusion, as a possible form of treatment for cutaneous habronemosis in the distal region of equine limbs. Materials, Methods & Results: Twelve horses were used, divided into two groups, with the left thoracic limb (LTL) being the test limb, and the right thoracic limb (RTL) the control limb. At moment zero (M0), distal radiography and venography were performed. The tourniquet was then loosened and after five minutes, at moment one (M1), the tourniquet was repositioned for 1.25 mg/kg (G1) and 5.5mg/kg (G2) trichlorfon injections into the left thoracic limb, diluted in 20 mL of Ringer's lactate solution, and 20 mL of Ringer's lactate solution was applied to the right thoracic limb. The tourniquet was maintained for 30 minutes after infusion in both groups. At moment two (M2), four days later, blood tests, radiography, and venography were repeated. Every day between M0 and M2, physical examinations were performed, including measurement of the pastern, fetlock, and coronet band, and a lameness examination. There were no significant alterations in clinical parameters, behavior, and appetite. In the blood cell count, there was an increase in leukocytes on D4 in G2, although remaining within the reference values for the species. The biochemical tests showed no alterations. There were no changes in the circumferences evaluated and 4 horses from G2 presented lameness in the LTL and one in the RTL. In the venograms, one G2 animal was noticed to be hypoperfused in all LTL plexuses. Discussion: The use of trichlorfon in regional perfusion at a dose of 1.25 mg/kg demonstrated safety, with no clinical, laboratory, and lameness changes in any of the animals. At the highest dose (5.5 mg/kg), individual reactions were observed, such as different degrees of lameness, swelling, and heat in foot. Serial venographies document the response to treatment used, it was decided to perform the second venography 4 days after the trichlorfon perfusion and the first initial venography evaluation, following the recommendations for the repetition time of the examination and evaluation of the use of the drug. The evaluation of radiographic images of venography, in a grading system created considering the range of contrast in five regions by the three examiners experienced in podiatry and the analysis of radiographic images of limbs of horses, without having participated in the previous procedures was important for the reliability of the assessment. The areas of hypoperfusion observed in the venography were not related to trichlorfon perfusion. It is essential that the application of trichlorfon be performed correctly, intravenously, to avoid reactions such as necrosis, pain, edema, erythema, lameness, and even more severe inflammatory reactions, such as phlegmon and thrombophlebitis. Although a small number of animals were used in this study, trichlorfon regional perfusion of equine limbs, at a dose of 1.25 mg/kg may be a technique appears to be inert to hoof vascularization.